1986
DOI: 10.1016/0035-9203(86)90265-8
|View full text |Cite
|
Sign up to set email alerts
|

Severe anaemia and death due to the pharyngeal leech Myxobdella africana

Abstract: Six cases of pharyngeal leech (identified as Myxobdella africana) are reported from a highland area of North Kenya. Three patients were severely anaemic and one died. There have been sporadic reports of leech infestation of man in East and Central Africa but these reports lack correct identification of the leech. This paper includes a detailed account of the systematics of the leech and of its habitat. The leeches were ingested accidentally by drinking water from two infested water sources. The major symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
1
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 4 publications
4
62
1
1
Order By: Relevance
“…Inside the host they may inhabit the upper respiratory tract [1][2][3] and cause a variety of symptoms, mainly epistaxis, bleeding from the mouth, nasal obstruction, foreign body sensation, stridor, dyspnea, and dysphagia, sometimes ending in death. 4 We report six cases of leech infestations of the upper respiratory and digestive tract from Jordan.…”
mentioning
confidence: 99%
“…Inside the host they may inhabit the upper respiratory tract [1][2][3] and cause a variety of symptoms, mainly epistaxis, bleeding from the mouth, nasal obstruction, foreign body sensation, stridor, dyspnea, and dysphagia, sometimes ending in death. 4 We report six cases of leech infestations of the upper respiratory and digestive tract from Jordan.…”
mentioning
confidence: 99%
“…Due to these mode of transmission almost all cases have been reported from less-developed countries in the rural areas or distant urban areas where use of safe water is often a problem 8 . When attached to the mucous membrane, they ingest blood averaging 10 times of their weight 9 . In this regard aquatic leeches are more dangerous than land leeches because they are more likely to cause severe anemia which may require blood transfusion 1 .…”
Section: Discussionmentioning
confidence: 99%
“…[1] Cundall et al [20] reported three patients with severe anemia, one of whom died. Our patient had suffered from weakness and anorectal pain for approximately four days, and a hypochromic microcytic anemia had developed, but he did not require blood transfusion.…”
Section: Discussionmentioning
confidence: 99%